Anna Götlind: The Messengers of Medieval Technology? Cistercians and technology in medieval Scandinavia (Victoria Bokförlag, 1990). 44 s. Appendices I-VI. - Linton, Michael (Historie/Jyske Samlinger, 1993)
-